Places in need: the changing geography of poverty - Allard, Scott W. (Russell Sage Foundation, 2017)
Introduction -- (Re)considering poverty and place in the U.S -- The changing geography of poverty in the U.S -- The local safety net response -- Understanding metropolitan social service safety nets -- Rethinking poverty, rethinking policy